Sensing nitriles with THz spectroscopy of urine vapours from cancers patients subject to chemotherapy - Vaks, Vladimir; Anfertev, Vladimir; Chernyaeva, Maria; Domracheva, Elena; Yablokov, Anton; Maslennikova, Anna; Zhelesnyak, Alla; Baranov, Alexei; Schevchenko, Yuliia; Pereira, Mauro Fernandes (Scientific reports, 2022)
A THz nonstationary high-resolution spectrometer based on semiconductor superlattice multipliers is applied to investigate the dynamics of urine composition for cancer patients treated with chemotherapy. The molecular urine composition of healthy volunteers and cancer patients was compared and contrasted. We have found a set of nitriles that either appeared after chemotherapy or increased in content, which are expected as a result of bio-chemical damage to the liver. While no damage can be detected at this stage by existing clinical methods, the identified nitriles are candidates for further large-scale systematic testing towards markers for nephrotoxicity of chemotherapy at an early stage of the treatment, when conventional diagnostics cannot identify substantial organ damage. Comparing the metabolite concentration dynamics with side effects during chemotherapy might then help individuate patients prone to severe complications and correct the treatment. Our devices are game-changers for THz spectroscopy of liquids: they allow spanning four different frequency ranges for a general evaluation of most substances found in the liquid and selecting a spectral interval that bypasses the strong absorption lines from substances such as water and ammonia, which may otherwise mask the detection of the target metabolites.